2004
DOI: 10.1161/01.cir.0000109213.10461.f6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Systolic and Diastolic Dysfunction After a Cholesterol-Rich Diet

Abstract: These data demonstrate that dietary hypercholesterolemia induces a "cholesterol cardiomyopathy" characterized by systolic and diastolic dysfunction. These alterations were independent of vascular disease and demonstrate a dietary link to cardiac dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
102
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 29 publications
4
102
1
2
Order By: Relevance
“…The recapitulation of the fetal gene program (i.e., an MHC isoform switch from predominantly ␣ to ␤, decreased SERCA2a, and increased ANP) classically occurs to varying extents in response to a number of mechanical insults, including thoracic aortic constriction (15,34), pacing-induced heart failure (52), and aortocaval shunting (37). However, there is a growing body of evidence that certain metabolic disturbances, including hypothyroidism (24), dexamethasone treatment (21), gonadectomy (57), and a high-cholesterol diet (32), produce these changes as well. In light of our findings, and those of others (14,39), it would appear that insulin-resistant diabetes is no different.…”
Section: Discussionmentioning
confidence: 99%
“…The recapitulation of the fetal gene program (i.e., an MHC isoform switch from predominantly ␣ to ␤, decreased SERCA2a, and increased ANP) classically occurs to varying extents in response to a number of mechanical insults, including thoracic aortic constriction (15,34), pacing-induced heart failure (52), and aortocaval shunting (37). However, there is a growing body of evidence that certain metabolic disturbances, including hypothyroidism (24), dexamethasone treatment (21), gonadectomy (57), and a high-cholesterol diet (32), produce these changes as well. In light of our findings, and those of others (14,39), it would appear that insulin-resistant diabetes is no different.…”
Section: Discussionmentioning
confidence: 99%
“…Although the gap junction remodeling proceeded the statistically significant reduction in CVI, Sm and impairment of Tei index, the presentation of temporal profile may not be enough to establish a cause-effect relation between them, because the myosin isoform redistribution and downregulation of SERCA-2 have been observed in the failing myocardium. 36 Further experiments will be required to disclose the critical role of contractile synchronism of normal myocytes in generating CVI.…”
Section: Discussionmentioning
confidence: 99%
“…However, these rabbit studies should be interpreted with caution. Indeed, plasma cholesterol levels in these studies were approximately 500 mg/dl [73] and 800 mg/dl [74], which is rarely observed in humans.…”
Section: Non-hdl Lipoproteinsmentioning
confidence: 67%
“…Data on the effect of cholesterol on in vivo systolic and diastolic function are paralleled by observations in isolated cardiomyocytes showing a decrease in the maximum rate of cardiomyocyte shortening and the maximum rate of cardiomyocyte 395 relaxation [74,75]. Based on these observations, the term 'cholesterol cardiomyopathy' has been introduced [74].…”
Section: Non-hdl Lipoproteinsmentioning
confidence: 96%
See 1 more Smart Citation